EFEKTIVITAS TEKNIK DESENSITISASI SISTEMATIS UNTUK MENGURANGI KECEMASAN BELAJAR SISWA KELAS VIII DI SMP NEGERI 7 TARAKAN TAHUN PELAJARAN 2018/2019 - Sandana, Maya; Rahmi, Siti (Jurnal Bimbingan dan Konseling Borneo, 2019)
This research aim to to know Effectiveness Technique of Desensitisasi Systematic To Lessen Dread Learn Student Class of VIII In SMP Country 7 Tarakan. Technique of Desensitisasi systematic is an technique to do change tune by focussed aid to client to make calm client of stress by teaching client for rileks in lessening emotional respon which worry. This research use quantitative approach of type of quasi-eksperimen with design group control nonequivalent desain. Research population amount to 230 student. Sampling technique the used is sampling purposive with rule of research sampel and obtained by 20 student which divided in experiment group and control group. used instrument in the form of dread scale learn which have passed test of validasi of judgement expert and expressed is valid. The mentioned strenghtened with statistical analysis result of calculation of test of ttest by using Statistical Product And Service Solution ( SPSS) Version 24.00 windows for obtained nby value of signifikansi = 0.000 = 0.05. this matter show value of signifikan less than 0,05 can be pulled [by] conclusion that hypothesis accepted, meaning that technique of desensitisasi effective systematic in lessening dread learn class student of VIII in SMP Country 7 Tarakan School Year 2018 / 2019. Keyword : Systematic Desensitisasi, Dread Learn.